1987
DOI: 10.1530/jrf.0.0800487
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of egg development and implantation in rats after post-coital administration of the progesterone antagonist RU 486

Abstract: RU 486 was administered to rats on Day 1 or Days 1 + 2 of pregnancy. Endometrial sensitivity (i.e. decidualization in response to oil instillation) was delayed by 2.5 mg/kg injected s.c. on Day 1, and almost half of the animals also exhibited a delay in implantation of 1-2 days. Higher doses (5 or 10 mg/kg) administered on Days 1 + 2 reduced the number of implantations to zero in all animals. Apparently normal morulae were found up to the evening of Day 4 in the oviduct and/or the uterus of most animals. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
2
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 4 publications
2
24
2
2
Order By: Relevance
“…It has been reported that postcoital administration of mifepristone modulates egg transport through the oviduct (Roblero, et al, 1987;Fuentealba, et al, 1987;Yang and Wu, 1990), retards early embryonic development (Psychoyos and Prapas, 1987;Roblero and Croxatto, 1991), delays endometrial maturation (Roblero and Croxatto, 1991;Batista, et al, 1992;Cameron, et al, 1996) and thereby inhibits or delays implantation (Psychoyos and Prapas, 1987;Roblero and Croxatto, 1991;Dao, et al, 1996). In the present study, treatment with 4 mg/kg mifepristone during the post-coital phase produced small numbers of live embryos and a high postimplantation embryonic mortality but did not reduce the number of implantations.…”
Section: Discussioncontrasting
confidence: 51%
“…It has been reported that postcoital administration of mifepristone modulates egg transport through the oviduct (Roblero, et al, 1987;Fuentealba, et al, 1987;Yang and Wu, 1990), retards early embryonic development (Psychoyos and Prapas, 1987;Roblero and Croxatto, 1991), delays endometrial maturation (Roblero and Croxatto, 1991;Batista, et al, 1992;Cameron, et al, 1996) and thereby inhibits or delays implantation (Psychoyos and Prapas, 1987;Roblero and Croxatto, 1991;Dao, et al, 1996). In the present study, treatment with 4 mg/kg mifepristone during the post-coital phase produced small numbers of live embryos and a high postimplantation embryonic mortality but did not reduce the number of implantations.…”
Section: Discussioncontrasting
confidence: 51%
“…We have earlier reported that monkey embryos exposed in vivo to mifepristone fail to yield evolutive implantation (Ghosh et al 1997). Psychoyos & Prapas (1987) observed that administration of mifepristone to rats on days 1 and 2 of pregnancy resulted in a blockade of the morula-to-blastocyst transition.…”
Section: Discussionmentioning
confidence: 95%
“…P mixta is used as a "morning after" remedy by women of Zimbabwe to prevent pregnancy (Sewani-Rusike 2010). In order for implantation to occur, especially in the rat, the exact equilibrium of estrogen and progesterone hormones must be attained to create a milieu ideal for implantation (Psychoyos and Prapas, 1987). Thus, P. mixta showed contraceptive activity with inhibition of implantation and fertility rates, ethanolic extract being more effective than the aqueous extract (Table 1) The rat endometrium is sensitive to blastocyst signals in the morning of day 5 (Singh and Kamboj, 1992), but can experience failure of blastocyst implantation due to hostile uterine environment or hypermotility (Hafez and Hafez, 2000;Emiliani et al, 2005).…”
Section: Discussionmentioning
confidence: 99%